PP.72 Reduced Fetal Movements - Has RCOG Guidance Been Translated into Practise?. (26th April 2013) - Jones, F; Saunders, A; Heazell, AEP; Whitworth, MK
Abstract : Background: NHS clinical effectiveness initiatives aim to promote uniform standards of high-quality evidence based care. Clinical practise guidelines produced by the RCOG are a principle component of such care. We aimed to determine if the publication of the RCOG guideline on 'Reduced Fetal Movements' (RFM), (Feb 2011) had translated into the development of evidence-based policies in maternity units in the UK. Methods: UK maternity units were asked to provide a copy of their guideline for the management of reduced fetal movements (May-July 2012). 12 audit criteria were agreed by committee, based on the strongest evidence in the RCOG RFM guideline. Guidelines were then audited to assess concurrence with these criteria. Results: Responses were obtained from 50% of units. 12 units had no guideline. The 101 remaining guidelines were of variable length (1–27 pages). 8 were out-of-date and 12 had no review date. Zero unit policies contained all 12 criteria taken from the RCOG guideline. The median number of audit criteria included in any guideline was 7 (26.7%) (range 3–11). The only criterion included in all the guidelines was 'After fetal viability has been confirmed…..the woman should have a CTG'. 11 units (10.9%) continue to recommend the use of kick charts. Conclusion: The translation of RCOG guidance into effective clinical practise is variable. Research is needed to determine how improvements can be made in this transition.